2018
DOI: 10.3310/hta22110
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of early pulmonary rehabilitation and activity after COPD exacerbations: external pilot randomised controlled trial, qualitative case study and exploratory economic evaluation

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) affects > 3 million people in the UK. Acute exacerbations of COPD (AECOPD) are the second most common reason for emergency hospital admission in the UK. Pulmonary rehabilitation is usual care for stable COPD but there is little evidence for early pulmonary rehabilitation (EPR) following AECOPD, either in hospital or immediately post discharge.ObjectiveTo assess the feasibility of recruiting patients, collecting data and delivering EPR to patients with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(62 citation statements)
references
References 176 publications
(263 reference statements)
2
59
0
1
Order By: Relevance
“…Overall, 5 of the 464 observed correlations were small (less than 0.10). Two of these small correlations came from the PRACTICE trial [26]. In this trial (PRACTICE) we observed a negative correlation of − 0.13 ( n = 36 participants) between the baseline and 3 months follow-up post-randomisation time point for the EQ-5D visual analogue scale (VAS) and 0.09 ( n = 42 participants) between the baseline and 1 month follow-up.…”
Section: Discussionmentioning
confidence: 93%
“…Overall, 5 of the 464 observed correlations were small (less than 0.10). Two of these small correlations came from the PRACTICE trial [26]. In this trial (PRACTICE) we observed a negative correlation of − 0.13 ( n = 36 participants) between the baseline and 3 months follow-up post-randomisation time point for the EQ-5D visual analogue scale (VAS) and 0.09 ( n = 42 participants) between the baseline and 1 month follow-up.…”
Section: Discussionmentioning
confidence: 93%
“…Of the studies included in this review, 19 (95%) were published in peer-reviewed journals [2][3][4]12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and 1 (5%) was a published abstract for which further information was obtained from the author 34 (see Supplemental Table S1). These 20 studies described 16 unique randomized controlled trials, [2][3][4]12,[19][20][21][22][23][24][25][26][29][30][31]34 and 2 were single-group studies. 28,33 Two studies were qualitative analyses which utilized responses from participants recruited to two of the randomized controlled trials.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the studies by Eaton and colleagues (21) and Greening and colleagues (22), 57% and 27% of the eligible patients, respectively, declined participation in PR after AECOPD. The authors of a recent randomized, controlled trial (23), where patients completed early PR either at the hospital or at their home after hospitalization due to an AECOPD, concluded that recruitment and delivery of the intervention at the hospital was difficult. In this study, the home program was more acceptable.…”
Section: Discussionmentioning
confidence: 99%